Estudo da sintaxe de ordem dos clíticos pronominais no vernáculo de missivistas mineiros altamente letrados - Elisete Eustáquia Rodrigues Silva (2021)
We present a descriptive study of the paradigm of the object pronouns order syntax in the morpho-syntactic context of the simple verb forms and verbal groups (compound time and verbal locution, in traditional terms), in the literate vernacular from Minas Gerais, represented here by the personal letters of three writers – Fernando Sabino, Otto Lara Resende e Murilo Rubião –, which were exchanged between the 40s and 70s of the 20th century. The main objective was to investigate in which extent the order syntax of pronominal clitics adopted by these speakers/writers approaches or takes distance from the standard norm of Brazil’s Portuguese Language (PB), represented here by three reference grammarians: Bechara (2009[1961]), Cegalla (2008[1964]) and Cunha and Cintra (2001[1984]). We explored the main hypothesis of that the pronominal order syntax used by highly literate citizens, in a context of informality, would take distance, to some extent, from the standard norm proposed in our normative grammars, which mirror themselves the European norm. Additionally, the following conjectures were tested, which have demonstrated, in this study, to be so relevant as the main hypothesis, once our dada are robust in relation to them: (i) there would be a common pronominal order syntax pattern for the three speakers/writers, considering the academic background similarity between them, their generational age and the bonds of friendship that linked them; (ii) the type of object pronouns and its respective syntactic functions would influence its order syntax; (iii) there could be a change in the pattern of use of these pronouns by the speakers/writers over the years; and the place where they lived (Rio de Janeiro and Belo Horizonte) would also determine an eventual variation in the pattern of use of the pronominal clitics in their letters. The investigation undertaken is of a qualiquantitative nature and it was based on the assumptions of Variationist Sociolinguistics (LABOV, 2008[1972]), by an adaptation of the panel study methodology, which examined the vernacular of the same speakers over four decades of the 20th century. A total of 390 occurrences of pronominal clitics was analyzed, of which 320 were in the syntactic context of a single verb and 70 were in the context of verbal group. The results achieved support the hypothesis that the pronominal order syntax used by highly literate speakers/writers takes distance from the standard norm of Brazilian Portuguese in some syntactic contexts, as well as there is a common pattern of the pronominal order syntax between them, which has changed over the four decades analyzed. The analysis undertaken also revealed that the type of pronominal clitic and the type of nominal form of the verb to which it is linked, to a certain extent, condition the proclitic or enclitic position of the object pronouns, but that their functions do not act as a determining factor of their order syntax.